The Reasons Behind the Rise of ISIS: An Analytical Perspective - Amer Ababakr (Mediterranean Journal of Social Sciences, 2022)
In June 2014, the Islamic State of Iraq and Syria (ISIS) surprised the international community by declaring the establishment of a self-proclaimed Islamic State in the territory of Iraq and Syria. There are several factors behind the rise of ISIS including; the political chaos in Iraq, which paved the way for ISIS to come up within the political struggle and conflict in the country. This is a clear indication that the Iraqi people need reconciliation and compromise more than any other time. The old sectarian tension between Sunnis and Shias in Iraq helped ISIS to capitalize anti-Shia rhetoric and sectarianize its war against Shia Militias in order to achieve the sympathy of the marginalized Sunni population. Meanwhile, some domestic, regional and international circumstances led to the fall of ISIS including lack of dependable allies, false claims and the threat of ISIS on Iraq and beyond pushed the international community to stand against the group. And they cooperated and collaborated with each other to form a coalition and this fact led to almost defeating ISIS in Iraq as a terrorist organization that held territory. Received: 13 July 2022 / Accepted: 26 August 2022 / Published: 2 September 2022